Ion intercalation dynamics of electrosynthesized mesoporous WO3 thin films studied by multi-scale coupled electrogravimetric methods1. Issue 22 (14th June 2015) - Razzaghi, Fatemeh; Debiemme-Chouvy, Catherine; Pillier, Françoise; Perrot, Hubert; Sel, Ozlem
<x xml:space="preserve">Abstract</x> Mesoporous WO3 thin films were prepared electrochemically by using an ionic surfactant during the synthesis, and the electrochemical properties are investigated in comparison with their dense analogues.